KESANTUNAN BERBAHASA RETORIC INTERPERSONAL MASYARAKAT SUNDA SEBAGAI ALTERNATIF PENGEMBANGAN BAHAN AJAR MATA KULIAH SOSIOLINGUISTIK - Kartini, Ari (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTIn general the studies to be conducted aims to develop learning the local culture, the culture of Sunda to be applied through character education in improving student politeness STKIP Garut. The plan of activities to be implemented in this study were 1); describe the situation on the ground regarding the rhetorical politeness interperonal Sundanese society; 2) conduct theoretical studies about the characteristics of interpersonal speaking of polite rhetoric in Sundanese cultural perspective; 3) applying the results of theoretical studies through the development of teaching materials Sosiolinguistik. This research is a qualitative research so that the method used is descriptive-analytic method. Where this penelian only describe and develop teaching materials and courses Sociolinguistics Pragmatics in STKIP Garut. The results of observations about the behavior of the public modesty hometown village Kudang Wanajaya Wanaraja Garut districts, showed that people's behavior Sunda "impolite". It can be seen from the observation indicated by the percentage calculation that is, 18.03% shows the scale (often), 52.17% was obtained at the scale of B (Sometimes), and Behavior on scale C (never) get a percentage 29.80%, which means that the Sundanese people never perform the behavior in accordance with the statements in the questionnaire. Meanwhile, the results recap the speech politeness interpersonal rhetoric of the analysis results in twelve events said there are 115 known utterance containing six maxims manners. utterances that contain maxims (-) a total of 52 speech and containing maxim manners (+) were 63 speech. It can be concluded, that in the speech analysis on aspects of language, society Sundanese village village Kudang Wanajaya Wanaraja Garut districts still holds intact politeness in communicating. This is consistent with the character of Sundanese culture that is now known to have cultural values (culture Values). In this case, the community is known as the Sunda religious society, soft, and very spiritual. This trend is born of compassion term penance, penance grindstones, reparation parenting. In addition, the behavior of the Sundanese people brimming with confidence; a language that knows no social inequality speaker with the speaker, but in general the railroad rafter Sundanese language is of the utmost importance.Key Words: Speak politeness, Interpersonal rhetoric, Sundanese culture